Association between Medical Adherence and Perception of Disease among Hypertensive Patients visiting a Tertiary Care Teaching Hospital - Raut, Binod; Poudel, Nimesh; Thapa, Devika (Journal of Institute of Medicine Nepal, 2024)
Introduction Medication adherence level is influenced by disease type and its severity, patient characteristics, socioeconomic factors, type of treatment and its regimen. Proper adherence to treatment is very important to obtain a higher therapeutic benefit. The aim of this study was to study the association between medical adherence and perception of disease among hypertensive patients. Methods It is a cross-sectional study involving 148 hypertensive patients based on convenience sampling technique conducted in the tertiary care Teaching hospital. Patients who have been taking antihypertensive medications for at least 6 months were enrolled. A structured questionnaire was used for data collection. JASP statistical software was used for data analysis. Results In this study 148 hypertensive patients taking medications were enrolled. Out of them, 54 (36.5%), 58 (39.2%) and 36 (24.3%) had low, medium and high level of adherence; while 94 (63.51%) 31 (20.95%) and 23 (15.54%) had perceived their disease as low, medium and high threat. Conclusion Medication adherence was found to be lower among the hypertensive patient, yet more than half had good perception. Regular monitoring and awareness program could be effective for the prevention of complications.